2017
DOI: 10.4103/ijc.ijc_203_17
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pictorial warning labels on tobacco products among patients attending outpatient department of a dental college in Bangalore city: A cross-sectional study

Abstract: The present study revealed that most of study participants have noticed the warnings on tobacco products, and most of them believe that they could understand warning labels. This study also showed that most of study participants believed that pictorial health warnings create awareness about probable health hazards of tobacco use and that these pictorial presentations on tobacco packs positively assist in reducing or quitting tobacco smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 7 publications
0
10
1
Order By: Relevance
“…Our study found lower levels of awareness of health warnings than previous studies in urban areas 10,12 , and a much lower proportion believing that the warnings would be effective in stopping tobacco use than in a previous report 10 . However, this latter comparison may be due to the much lower proportion of current users in our sample.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Our study found lower levels of awareness of health warnings than previous studies in urban areas 10,12 , and a much lower proportion believing that the warnings would be effective in stopping tobacco use than in a previous report 10 . However, this latter comparison may be due to the much lower proportion of current users in our sample.…”
Section: Discussioncontrasting
confidence: 95%
“…Previous research into awareness of health warnings on tobacco products in India has been carried out among the general public 10 , tobacco users 11 and hospital patients 12 , but these studies all pre-date the introduction of 85% health warnings in 2016. Our study found lower levels of awareness of health warnings than previous studies in urban areas 10,12 , and a much lower proportion believing that the warnings would be effective in stopping tobacco use than in a previous report 10 .…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, a total of 22.3% of the world's population were tobacco users, with 36.7% of men and 7.8% of women [ 9 - 11 ]. All in all, tobacco use is one of the major preventable causes of death worldwide [ 5 ].…”
Section: Reviewmentioning
confidence: 99%
“…and "How do you feel when you read the text warning?" Answers to these questions are typically given using words such as "worried," "not to start," "like limiting," "like giving up smoking," and "nothing" [ 5 , 18 , 27 ]. The study found that people who had seen the graphic health warnings were more likely to have a positive attitude toward not smoking.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation